Secrets of Tut's Tomb and The Pyramids - Stephanie Reiff (USA Contemporary Perspectives, 1977)
Discusses the building of the Egyptian pyramids, strange stories associated with them, and possible powers possessed by pyramids.
Keywords: History, Geography and Archaeology (3GdJGQjN hGdLZQGajG hGdBKGQs; Pyramids -- Juvenile literature; General